Program Penguatan Moderasi Beragama Menuju Indonesia yang Rukun, Damai dan Toleran di Lingkungan Kementerian Agama Kota Mojokerto - Hasan, Ismail (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2022)
Islam is a religion that came as rahmatallil alamin or as a mercy for all nature. His arrival is expected to bring love, happiness and perfect peace both in this world and in the hereafter. Along with the development Islam, the world also continues to experience developments in various aspects. There are three challenges in the MB strengthening process. First, development of excessive, overreaching, and extreme religious understanding and practice, the second challenge, emergence truth claims on religious interpretations. The third challenge is an understanding that actually undermines or threatens, even destroys national bonds.